Secukinumab as a potential trigger of inflammatory bowel disease in ankylosing spondylitis or psoriatic arthritis patients. (2nd March 2021) - Onac, Ioana A; Clarke, Benjamin D; Tacu, Cristina; Lloyd, Mark; Hajela, Vijay; Batty, Thomas; Thoroughgood, Jamie; Smith, Sandra; Irvine, Hannah; Hill, Diane; Baxter, Grace; Horwood, Natalie; et al.
Abstract: Objective: Real-world secukinumab gastrointestinal-related adverse events (GIRAE) data during treatment for AS and PsA are lacking. We aimed to obtain this through baseline evaluation of pre-existing IBD rates and predictors of GIRAE. Methods: Patient electronic and paper records commencing secukinumab from 10 UK hospitals between 2016 and 2019 were reviewed. GIRAE after initiation were defined as: definite [objective evidence of IBD (biopsy proven), clear temporal association, resolution of symptoms on drug withdrawal, no alternative explanation felt more likely], probable (as per definite, but without biopsy confirmation) or possible (gastrointestinal symptoms not fulfilling definite or probable criteria). Results: Data for all 306 patients started on secukinumab were analysed: 124 (40.5%) AS and 182 (59.5%) PsA. Twenty-four of 306 (7.8%) experienced GIRAE after starting secukinumab. Amongst patients who developed GIRAE, four (1.3%) had definite, seven (2.3%) probable and 13 (4.2%) possible IBD. All definite cases were patients with AS and stopped secukinumab; two had pre-existing IBD and two (0.7%) were de novo cases of which one required surgical intervention. Seven patients (2.3%) had pre-existing diagnoses of IBD prior to initiation, of which five patients experienced GIRAE. Conclusion: Absolute rates of new IBD in patients starting secukinumab are low. The majority of patients developing new GIRAE did not develop objective evidence of IBD or stop therapy. For patients with pre-existing IBD and AS the risk of GIRAE is much higher, and prescribing alternatives should be considered.